Chemical Treatment of Jordanian Zeolitic Tuff Using Dimethyl Sulfoxide and Thiourea - N. AMRO., ABDULAZIZ; I. YOUSEF., RUSHDI; M. MUSLEH, SALEM (Asian Journal of Chemistry, 2010)
Jordanian zeolitic tuff was chemically treated with dimethyl sulfoxide and thiourea. The treated and untreated zeolitic tuff samples were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF) and scanning electron microscopy (SEM). The XRD and XRF results showed that the chemical treatments using dimethyl sulfoxide and thiourea do not change neither the mineral constituents nor the Al2O3 and SiO2 contents of the zeolitic tuff. The SEM figures showed clearly loading amounts of both dimethyl sulfoxide and thiourea on the zeolitic tuff surface. The ability of treated and untreated zeolitic tuff samples to remove some heavy metals ions from their acidic aqueous solutions was investigated. The results revealed that treatment with thiourea enhances the tuff ability for Pb(II), Cd(II), Zn(II) and Ni(II) cations uptake. In general, the metals uptake by zeolitic samples was found to decreased in the order Pb(II) > Cd(II) > Zn(II) > Ni(II).